CONTEMPORARY HINDI DRAMA: INTRODUCTION AND TRENDS - Rai, Shashikant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Today, time is changing very fast and along with time, social, economic, political, literary etc. values ​​are also changing. With the development of human civilization, it is natural for its environment and changes to take place. This change takes place both internally and externally. It is worth noting how much more humane, sensitive and democratic this change is. Literature determines its values ​​by testing all these criteria. Change is the eternal law of nature. It is natural for a person to change in every way, but in contemporary times, questions can be raised about the nature of change. Because if the change is in its entirety and democratic, then it is fine, but if it is of a particular class, of a particular group, then it is natural to have questions. Therefore, the challenges of contemporary literature emerge in front of us very fast. Literature also plays an important role in this social change. The tendencies of society are expressed through contemporary and contemporary literature. The basic idea behind the creation of a drama is the change in human relations within society and the consequences of that change. The usefulness of literature is proved only in taking the welfare of the people to the highest level keeping in mind the contemporary values ​​of life.